2019
DOI: 10.1021/acs.jpcc.9b09418
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Optoacoustic Spectroscopy Studies of Inorganic Functionalized Metallic Nanorods

Abstract: Plasmonic nanoparticles can be used in photothermal therapy thanks to their ability to generate local heat. The light-to-heat conversion efficiency is crucial for therapeutic and diagnostic applications. The photothermal properties of gold nanorods functionalized with silica layers of controllable thickness were characterized using both theoretical and experimental approaches. The time-resolved laser-induced optoacoustic spectroscopy (LIOAS) was used to determine the amount of absorbed energy that changed prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…A further analysis unveils that the Δ T is tightly correlated to the p ( r ) value of the Au NP, indicating that a Au NP with larger absorption power density could cause higher Δ T at the LSPR excitation. The calculated Δ T maximum of the AuSP is in good agreement with the results previously reported in the literature with a similar particulate size. Again, the Au NPs with sharp structural features such as AuNR, AuST, and AuBP exhibit obviously higher Δ T maximum than AuSP and AuNC, which is consistent with the change trend of their Jo numbers. We have shown that an increase in the N Au could red-shift the LSPR wavelength along with a slight decrease of the near-field enhancement, but it causes significant decrease of the Jo number, especially for AuNR, AuST, and AuBP.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…A further analysis unveils that the Δ T is tightly correlated to the p ( r ) value of the Au NP, indicating that a Au NP with larger absorption power density could cause higher Δ T at the LSPR excitation. The calculated Δ T maximum of the AuSP is in good agreement with the results previously reported in the literature with a similar particulate size. Again, the Au NPs with sharp structural features such as AuNR, AuST, and AuBP exhibit obviously higher Δ T maximum than AuSP and AuNC, which is consistent with the change trend of their Jo numbers. We have shown that an increase in the N Au could red-shift the LSPR wavelength along with a slight decrease of the near-field enhancement, but it causes significant decrease of the Jo number, especially for AuNR, AuST, and AuBP.…”
supporting
confidence: 90%
“…In addition, we also found that the σ abs /σ ext ratio is almost constant at N Au < 5.0 × 10 5 but obviously decreases with an increase in N Au when N Au exceeds 1.0 × 10 6 for all these different shaped Au NPs (Figure S6B). It can be explained that the optical scattering becomes more obvious at a larger particle size, which decreases the light-to-heat conversion efficiency. , A comparison analysis further reveals that the change of the Jo number does not follow the change of the σ abs (Figure D­(ii)). This is mainly ascribed to the distinct geometric dependence of the σ abs of these Au NPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The finite integration technique was used to calculate the scattering yields (ϕ sc ) of Au-NRs@SiO 2 . The details and methodology of simulation are given in our previous work. Taking into account the dimensions of Au-NRs@SiO 2 from the analysis of TEM images, the optical extinction and radar cross sections (i.e., ECS, RCS respectively) were calculated. ϕ sc was determined by the relative contribution of RCS to ECS.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous approach for the Au-NRs was used. 13 All of the simulations presented in this paper used a frequency domain solver with a tetrahedral mesh. We used a tetrahedral mesh of about 58000 cells.…”
Section: Surface Film Preparation Andmentioning
confidence: 99%